Komunikasi Media Sebagai Kontrol Kebijakan Publik Pemerintah Kabupaten Pati Jawa Tengah (Analisis Teori Media Baru) - Muslimin Ritonga; Hafidz Khoiril Murtadho; Dewi Sartina (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
This study aims to analyze how digital technology can influence and provide control over public policy in the Pati Regency Government, Central Java. It explores how information disseminated across various social media platforms can capture public attention, particularly in Pati Regency, using the theory of new media communication. The rapid advancement of technology today has empowered the public to voice criticism, exercise policy oversight, and influence government decision-making in public policy. Therefore, the author is interested in examining Media Communication as a Tool for Public Policy Control in the Pati Regency Government, Central Java. With the development of information and communication technology, the public sphere has expanded, enabling greater opportunities for criticism, suggestions, supervision, and control over public policies. This research employs a qualitative method in the form of library research, utilizing books and other literature sources. The focus of this study is media communication as a means of policy control in the Pati Regency Government. It investigates the significant role of media in overseeing public policy, particularly in the Pati Regency of Central Java.